Histological study of wounded skin of diabetic rats treated with topical aqueous methanol extract of hibiscus rosa sinensis leaves / Nor Zahidah Tajjudin - Tajjudin, Nor Zahidah (2015)
Wound healing involves restoration of the injured tissues to its normal function and structure. However, wound healing in diabetic patients are impaired and delayed. The present study aims to investigate the macro- and microscopic changes of diabetic wounded skin after treated with aqueous methanol extract (MeOH) of Hibiscus rosa sinensis leaves. Fifty rats were used in the study that were randomly divided into four groups with 5 rats in the normal control group and 15 rats each in the negative control, positive control and treatment groups. Except for the rats in the normal control group, all other rats were streptozocin induced-diabetic and received a wound (2 cm x 2 cm) on the thoracolumbar spine. Topical silver sulphadiazine served as the treatment in the positive control group, while wounded rats in the negative control group were left untreated. The treatment group received 0.3 ml of 10 mg/kg MeOH extract. The treatment was provided daily. On the 3rd, 7th and 14th day of the study, a group consisting of five rats from the positive and negative control and the treatment groups were sacrificed. Our findings showed that rats that were treated with Hibiscus rosa sinensis MeOH extract showed significant improvement in wound closure in addition to absence of exudate or signs of infection. Histologically, improved structural changes by an elevation of well-arranged collagen fiber and increment of fibroblast accumulation were noted in the treatment group. As a conclusion, Hibiscus rosa sinensis MeOH extract may improve wound healing in diabetic rats, and may have potential as an alternative treatment for wound healing.